ACADEMIC EMOTION ON EFL EXTENSIVE READING PROGRAM ACROSS GENRES - Areta Puspa (Kopertis Region IV Jabar and Banten, 2022)
This present study monitors the EFL students’ emotions on extensive reading program across three genres, to be precise factual text and literary text. The data are collected from questionnaire, students’ diaries, and interviews to University students in Indonesia. The close-ended questionnaire are analysed through Path analysis. Moreover, the students’ diaries and interview are analysed by content analysis. Piloting from Pekrun’s emotions, the study directs into achievement emotion, epistemic emotion, topic emotion, and social emotion. This mix method study gains the students in arranging their emotion on extensive reading program as long as three months. This study seeks to contribute to unearth the students’ feeling maps across two genres, thus shedding lights on determining teaching methodologies appropriate to comply with typical emotions in certain genres for more active students’ engagement.